International review of cytology : a survey of cell biology. - Jeon, Kwang W. (International review of cytology, 1998)
International Review of Cytology presents current advances and comprehensive reviews in cell biology-both plant and animal. Articles address structure and control of gene expression, nucleocytoplasmic interactions, control of cell development and differentiation, and cell transformation and growth. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. Key Features * Acetabularia * The Role of the Dynactin Complex in Intracellular Motility * Dual Mechanisms of Apoptosis Induction by Cytotoxic Lymphocytes * Drought-Induced Responses in Plant Cells * Peptidergic Control of the Corpus Cardiacum-Copora Allata Complex of Locusts.